1998
DOI: 10.1089/omi.1.1998.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Genescapes: Phyletic and Functional Patterns of ORF Distribution among Prokaryotes

Abstract: We have implemented a statistically based approach to comparative genomics that allows us to define and characterize distributional patterns of conceptually translated open reading frames (ORFs) at different confidence levels based on pairwise FASTA matches. In this report, we apply this methodology to nine microbial genomes, focusing particularly on phyletic and functional patterns of ORF distribution within and between the two prokaryotic domains of life, Bacteria and Archaea. We examine patterns of presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 58 publications
2
64
0
Order By: Relevance
“…1,030 ORFs produce matches in the Aeropyrum pernix genome (at e Ͻ 10 Ϫ10 ), and 45 of these match A. pernix, exclusively, in the GenBank͞European Molecular Biology Laboratory database. Three hundred fifty seven Sulfolobus ORFs produce a match among bacteria but not eukarya, whereas 67 match eukarya but not bacteria at inclusion and exclusion thresholds e ϭ 10 Ϫ10 and 10 Ϫ5 , respectively (11,12). An additional 701 ORFs give a match in both domains.…”
Section: Genome Sequencing Organization and Annotationmentioning
confidence: 99%
“…1,030 ORFs produce matches in the Aeropyrum pernix genome (at e Ͻ 10 Ϫ10 ), and 45 of these match A. pernix, exclusively, in the GenBank͞European Molecular Biology Laboratory database. Three hundred fifty seven Sulfolobus ORFs produce a match among bacteria but not eukarya, whereas 67 match eukarya but not bacteria at inclusion and exclusion thresholds e ϭ 10 Ϫ10 and 10 Ϫ5 , respectively (11,12). An additional 701 ORFs give a match in both domains.…”
Section: Genome Sequencing Organization and Annotationmentioning
confidence: 99%
“…Many studies have focused on specific aspects of genome evolution or have tried to reconstruct a specific ancestral genome (Bruccoleri et al 1998;de Rosa and Labedan 1998;Huynen and Bork 1998;Kyrpides et al 1999;Makarova et al 1999;Aravind et al 2000;Ochman and Jones 2000;Jordan et al 2001). Large-scale studies on the presence and absence of genes have shown that the number of shared genes between genomes depends on the size of genomes (Snel et al 1999), and their evolutionary distance (Gaasterland and Ragan 1998;Huynen and Bork 1998;Fitz-Gibbon and House 1999;Snel et al 1999;Tekaia et al 1999). Correlation in the presence of genes has been used to predict functional interactions between genes (Pellegrini et al 1999;Huynen and Snel 2000).…”
mentioning
confidence: 99%
“…A group of genes with the same phylogenetic profile is assumed to encode proteins that are functionally related (for example, they may be part of the same metabolic pathway) and that may or may not interact physically. The drawback of the method is that it can only be applied to complete genomes [83,84]. Conservation of gene neighborhood.…”
Section: Discussionmentioning
confidence: 99%